ASSESSMENT OF PROGRAM HANDICRAFTS AT UNIVERSITIES OF THIRD AGE IN NITRA - SIRKA, Jan (Trends in education, 2012)
The Department of Technics and Information Technologies, School of Education, Constantine the Philosopher in Nitra, has conducted a research on examining the attibutes of life quality, as well as on examining the life quality itself of the adults and seniors attending the University of the Third Age. The data collected from our research have been compared with the data from the research conducted at the Comenius University in Bratislava and Philosophical Faculty of Presov University. We came to the conclusion that it is essential to create the environment and programmes that would enable the aging people and seniors to come to terms with new knowledge and information, that leads to maintaining and developing their skills, contributes to their handling of the modern society demands and fulfils their interests and needs.
Keywords: quality of Life; University of Third Age; crafts; motivation; collective; wood; tinker.